PEMANFAATAN TEKNOLOGI DIGITAL UNTUK PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KECAMATAN BABALAN - Eddi Suprayitno; Yusrita Yusrita; Antoni Antoni; Andina Mei Vani Lubis; Mutia Chairunisa (Universitas Islam Sumatear Utara, 2022)
One of the business fields that remains consistent and developing in the national economy, one of which is Micro, Small, and Medium Enterprises (MSMEs). With the rise of business growth, market competition is getting tougher. So that this situation forces business actors to optimize productivity and marketing strategies. Information technology is currently one of the potentials that of course can be utilized by MSMEs to be able to increase the marketing productivity of their business. Digital marketing is one of the information technologies that is currently developing rapidly, namely by utilizing technology and social media which are considered very potential in encouraging the development of MSMEs. Observations in several areas in Langkat Regency, namely in the Subdistrict, were carried out to observe the increase in business since the pandemic, this program aims to increase the profit income of MSMEs. The MSME Product Digitalization Program needs to be socialized to provide knowledge for the community in the Langkat Regency area, precisely in Babalan District about the benefits of digitalization of MSME Products which aims to provide knowledge to the public about digital marketing in order to increase profits for MSME business people, this program is a solution when profits from MSME business owners decline after being hit by the Covid-19 pandemic.